EXISTENCE OF THE MAX WEB BUREAUCRATIC CONCEPT AS AGENT OF CHANGE 0F BUREAUCRATION REFORM IN INDONESIA - Afifuddin Afifuddin (Ji_Mild (Jurnal Ilmiah Magister Ilmu Administrasi), 2019)
In the time when the reformation era begins, various issues or thoughts were raised by experts related to how to achieve good governance, including bureaucratic reform. These efforts are gradually carried out not only by the central government but also the regional governments (Provinces and Districts/Cities).Empirically, the bureaucracy is identical with the government civil servant which has three dimensions of organization, human resources, and management (Kristiadi in Thoha and Agus Dharma, 1999). In government, the dimensions are known as institutions, staffing and management, which are elements of state administration; presumably these dimensions can be added to the culture / mind set.The legal rational concept of Max Weber's bureaucracy is actualized in Indonesia with various disadvantages and advantages as seen from bureaucratic behavior. This bureaucratic behavior arises when interactions occur between individual characteristics and bureaucratic characteristics, moreover, with the developing issues and current law enforcement related to bureaucratic pathology.Gradually in Indonesia, bureaucratic reform is carried out in the institutional dimension, civil servants and management resources, both by the central government and regional governments. Moreover, it is in line with the statement written in Law Number 17 of 2007 concerning about the National Long Term Development Plan for 2005-2025 which states that: "The development of state civil servant is carried out through bureaucratic reform to improve the professionalism of the state apparatus and to realize good governance, both at the center and in the regions".In relation to the bureaucracy reform, the central government regulates legislation known as the pillars of bureaucratic reform namely: 1) the Public Service Bill; 2) Government Administration Bill; 3) State Administration Ethics Bill; 4) State Civil Service Bill; 5) State Ministry Bill; 6) Draft Bill on Authority Relations between the Central Government and Regional Governments; 7) Public/Nonprofit Service Agency Bill; 8) National Oversight System Bill; and 9) State Administration Accountability Bill.